2016
DOI: 10.1016/j.orgel.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Solution aging and degradation of a transparent conducting polymer dispersion

Abstract: a b s t r a c tAs organic electronics improve, there is increased research interest on the longevity and stability of both the device and individual material components. Most of these studies focus on post deposition degradation and aging of the film. In this article, we examine the stability of polyelectrolyte dispersions before film coating. We observe substantial differences in the solution properties of the transparent conducting polymer, S-P3MEET, when comparing fresh versus aged dispersions and relate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…29 A scanning tunneling microscopy study showed that PEDOT:PSS films have a phase-separated structure, resulting in anisotropic conductivity. 30,31 PEDOT:PSS films also have anisotropic optical properties due to their ordinary and extraordinary complex refractive index. 32 Furthermore, reports show that inverted PSCs based on PEDOT:PSS provide low V OC and short circuit current density (J SC ) due to the mismatched work function between PEDOT:PSS and the perovskite energy level.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 A scanning tunneling microscopy study showed that PEDOT:PSS films have a phase-separated structure, resulting in anisotropic conductivity. 30,31 PEDOT:PSS films also have anisotropic optical properties due to their ordinary and extraordinary complex refractive index. 32 Furthermore, reports show that inverted PSCs based on PEDOT:PSS provide low V OC and short circuit current density (J SC ) due to the mismatched work function between PEDOT:PSS and the perovskite energy level.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structure of poly(thiophene-3-[2-(2-methoxyethoxy)ethoxy]-2,5-diyl) (S-P3MEET) mimics that of PEDOT: PSS; 30,31 however, the S-P3MEET polymer has never been taken into consideration as an HTL for inverted PSC devices. Herein, S-P3MEET was investigated as a new HTL for inverted planar triple-cation perovskite solar cells due to its self-doping ability, in which the polymer and its sulfonate moieties do not have phase separation like PEDOT:PSS HTLs do.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In PEDOT:PSS, electrical charges hop between the PEDOT-rich phases across the insulating PSS phase 8 so that high variability in the processed morphology and physical properties of PEDOT:PSS leads to high variability in the electrical behavior. 9,10 Solvent additives and film post-treatment with secondary dopants have been shown to improve the electrical conductivity of PEDOT:PSS by aligning PEDOT centers. 1,1113 However, this approach also decreases the effective Seebeck coefficient of the resulting CP.…”
Section: Introductionmentioning
confidence: 99%